Damage to Families Facing Domestic Violence in Bungokho Sub-county Mbale District - Birungi Phelister (Uganda Christian University, 2024)
The study aimed to assess the damage to families experiencing ongoing domestic violence in Bungokho Sub-county, Mbale District, using a cross-sectional survey design with a sample size of 36 respondents. The findings revealed that 70% of the respondents reported various forms of domestic violence, including physical, emotional, and psychological abuse. It also revealed that 55% of families experienced significant physical and psychological damages due to domestic violence. Furthermore, the study found that 60% of respondents identified limited access to support services as a major barrier in addressing domestic violence. The study concluded that while some interventions are in place, they are insufficient to effectively reduce domestic violence. It further concluded that more comprehensive and accessible support services are needed. The study also concluded that increasing community awareness and involvement could enhance the effectiveness of interventions. Recommendations include expanding support services and increasing community engagement to address domestic violence more effectively. Additionally, the study recommended strengthening collaboration among local authorities, community leaders, and organizations to improve responses to domestic violence and develop more effective intervention strategies.
N/A